Messa in scena e ripetizione dell'identico: l'attesa d'amore come performance (Mantichora. Italian Journal of Performance Studies, 2020)
In literature as well as in everyday life, love waiting is an act, a play, a theatre monologue, a performance. For the waiting lover, the rhythm of his waiting is measured by an almost ritual repetition of thoughts, acts, conjectures, tics, manias. Independently of its duration or extent – it may be the long waiting for the beloved’s homecoming as well as the agitated ‘micro-waiting’ for the post or phone ring – love waiting is a continuous repetition, although customised from time to time, of the identical process. Consciously or not, the lover seems to conform to a sort of ‘play script’ of love waiting which is carved in the emotional heritage of humanity and is always played, with infinitely many small variations, in literature. Following the definition of love waiting proposed by Roland Barthes in Fragments d’un discours amoureux, the paper aims to detect and define the performative elements of love waiting and to verify their real presence in some XX century and contemporary pieces and novels that represent this particular kind of waiting.